The impact of genital lichen sclerosus and lichen planus on quality of life: A review. Issue 3 (18th August 2022) - Ranum, Alison; Pearson, David R.
Abstract : Background: Lichen sclerosus (LS) and lichen planus (LP) are inflammatory diseases that demonstrate genital and extra-genital manifestations. Genital involvement may result in pruritus, sexual dysfunction, pain, and irritation. It is intuitive that the severity of symptoms may result in functional impairment and emotional distress, leading to a reduction in quality of life (QoL). Objective: Investigate the current literature on the impact of genital LS and LP on QoL. Methods: A literature review was performed using PubMed and results were summarized. Articles published between 1994 and 2020 were screened and reviewed by both the authors. Results: These diseases have been assessed with dermatological assessments, such as the Skindex-29 and the Dermatology Life Quality Index, general health surveys such as the Short Form-12 questionnaire, and mental health instruments including the Beck Depression Inventory, and others; these instruments consistently demonstrate impaired QoL. It follows that treatment may reduce these symptoms. Interventions, such as photodynamic therapy, have demonstrated improvement in the depressive symptoms that impact QoL. Although both females and males experience a reduction in QoL related to these diseases, they experience the symptomatology differently. Through interviewing, male patients were more likely to report no symptoms compared with female patients, while female patients were also more likely to report worse QoL in the work-school domain of the Dermatology Life Quality Index as compared with male patients. Limitations: Few studies have addressed the effect of disease severity or treatment on QoL. Conclusions: Understanding how genital LS and LP contribute to reduced QoL for patients is critical for health care providers to better prioritize treatment strategies. Future prospective studies should investigate how QoL correlates with disease severity and response to treatment.